Drinking to thirst influences fluid replacement in adolescents judokas - Nathália Mayume Moreira Hayakawa; Raul Canestri Galvino Reis; João Paulo Lima de Oliveira; Juciane de Abreu Ribeiro Pereira; Wilson César de Abreu (Universidade Estadual Paulista (UNESP), 2018)
Abstract AIM The aim of this study was to examine the influence of the type of beverage and the use of thirst sensation to guide fluid replacement in the adolescent judokas. METHODS Nine male judokas aged 10-16 (average age 11,8 ± 4,0 years old) were submitted to a standardized training of 90 minutes. In the first phase of the study, the athletes completed the training with ingestion ad libitum of different beverages: day 1 (water) and after 48 hours, day 2 (sports drink). In the second phase, after 7 days of first stage, the athletes completed the training with ingestion of water or sports drink, guided by thirst sensation. The total volume of liquids ingested (VI) during the training was quantified and the level of dehydration was determined by variation of body weight before and after training (∆W). At the end of each training, the athletes were asked about the training intensity to determine perceived exertion (PE). RESULTS No differences were observed in weight loss (∆W) (range: -0,04 ± 0,4 to -0,69 ± 1,1 %) and perceived exertion (range: 3,2 to 5,0). The use of thirst sensation to guide fluid replacement reduced the total fluid intake when the beverage offered was the sports drink (no thirst vs. thirst sensation, 521,1 ± 290 vs 152,2 ± 187 mL - p=0,006). CONCLUSION The results suggest that fluid replacement guided by thirst sensation can be influenced by the type of beverage offered.